Study Analisis Elemen Tetrahedron dan Hexahedron Plat Tulang Material Magnesium AZ31B dengan Finite Element Method (FEM) - Mahruri Arif Wicaksono; Irza Sukmana (P3M Politeknik Negeri Cilacap, 2022)
Metallic-based materials are commonly used as bone plates as well as orthopedic implants, due to their mechanical properties. This study aims to perform a finite element analysis based on three-point bending test data according to the ASTM F382-99 standard. The dimensions of bone plate material was 120 mm x 14 mm x 5 mm (length x width x thickness) with 6 and 10 screw holes. The load given to the plate analysis was 986.89 N with element size of 0.55 mm. The hexahedron elements have the total number of 62,179 elements for 6 holes and 62,960 elements for 10 holes. The total number of elements of the tetrahedron were 63,609 elements for 6 holes and 64,822 elements for 10 holes. Also, finite element analysis for plates with 6 holes and 10 holes using hexahedron elements yielded a total deformation of 6.1963 mm and 6.7852 mm, respectively. Furthermore, the tetrahedron element for plates with 6 holes and 10 holes resulted in a total deformation of 6.1762 mm and 6.7651 mm, respectively. Based on the above data, it can be concluded that the finite element analysis calculation for bone plate using hexahedron elements is more accurate when compare to the tetrahedrons.